Squamous cell carcinoma of the renal pelvis—a rare case report - Hsu, Chia-Jung; Lee, Hsin-Hua; Shen, Jung-Tsung; Tsai, Kun-Bow; Huang, Chih-Jen (Therapeutic Radiology and Oncology, 2018)
Squamous cell carcinoma (SCC) of the renal pelvis is a rare cancer with a extremely poor prognosis. Its incidence is only 0.5–1% of all urothelial cancers. In most patients’ cases, SCC of the renal pelvis is associated with long-term renal calculi. We report a case of renal pelvic SCC patient developing disseminated metastatic disease rapidly. There are still no standard treatments for SCC of the renal pelvis. Some literature suggests the primary treatment of renal pelvic SCC is nephrectomy. Adjuvant chemotherapy or radiotherapy, though presents no concrete evidence of survival benefits, may still play a role for the control of local symptoms. New treatment modalities of patients with renal pelvic SCC and efforts at improving the accuracy of diagnosis at presentation are warranted.